CT based grain size analyses of Lake Lauvitel sediments - Laurent Fouinat; Pierre Sabatier; Jérôme Poulenard; Jean-Louis Reyss; Xavier Montet; Fabien Arnaud (PANGAEA, 2017)
Over the past decades, X-ray computed tomography (CT) has been increasingly applied in the geosciences community. CT scanning is a rapid, non-destructive method allowing the assessment of relative density of clasts in natural archives samples. This study focuses on the use of this method to explore instantaneous deposits as major contributors to sedimentation of high-elevation lakes in the Alps, such as the Lake Lauvitel system (western French Alps). This lake is located within a very steep valley prone to episodic flooding and features gullies ending in the lake. This variety of erosion processes leads to deposition of sedimentary layers with distinct clastic properties. We identified 18 turbidites and 15 layers of poorly sorted fine sediment associated with the presence of gravels since AD1880. These deposits are respectively interpreted as being induced by flood and wet avalanche. This constitutes a valuable record from a region where few historical records exist. This CT scan approach is suitable for instantaneous deposit identification to reconstruct past evolution and may be applicable to a wider variety of sedimentary archives alongside existing approaches.
Supplement to: Fouinat, L et al. (2017): A new CT scan methodology to characterize a small aggregation gravel clast contained in a soft sediment matrix. Earth Surface Dynamics, 5(1), 199-209, https://doi.org/10.5194/esurf-5-199-2017